Concordance of chronic conditions among the household members in Shanghai: a cross-sectional study - Jia He; Yingyi Qin; Yibin Guo; Yuanjun Tang; Cheng Wu; Xinji Zhang; Qian He (BMJ Open)
Objectives Members living in the same household tend to share some similar behaviours and environment. We want to quantitatively assess the associations of chronic conditions to investigate the concordance of disease status among the household members.Setting Shanghai, China.Participants Our data were from the fifth Health Service Survey in Shanghai in 2013. 12 002 households with 31 531 residents were selected in this survey by using a three-stage, stratified, random sampling method.Outcome measures Five highly prevalent chronic conditions, namely hypertension, diabetes, ischaemic heart disease (IHD), cerebrovascular disease (CVD) and obesity were chosen. The generalised estimating equations (GEE) model was used to estimate the associations adjusted for age, gender, education status, health insurance status, smoking and drinking. Using a subsample of adult children with parents’ chronic conditions as the key risk factor and a subsample of wives with the chronic conditions of the husband as key risk factor, we reran our GEE models to explore chronic condition concordance within these relationships.Results A total of 10 198 households with 27 010 adult participants were included. Using all adult household members, we found positive statistically significant associations between one’s chronic conditions and the same disease status of their household members (hypertension (OR=3.26, 95% CI 3.02 to 3.52); diabetes (OR=1.68, 95% CI 1.40 to 2.01); IHD (OR=5.31, 95% CI 3.56 to 7.92); CVD (OR=3.40, 95% CI 1.99 to 5.80); obesity (OR=3.41, 95% CI 2.34 to 4.96)). The results of analysing ad-child subsample and spouse subsample also showed similar associations. Moreover, the potential concordance of different chronic conditions was found between hypertension and diabetes.Conclusions We found chronic condition concordance within households. This study provides evidence that the chronic conditions of other members of a household may be a significant risk factor for a household member’s own health.